Road lighting and distraction whilst driving: Establishing the significant types of distraction. (January 2021) - Robbins, CJ; Fotios, S
There is a body of research showing how changes in lighting conditions affect hazard detection in the context of driving after dark. There is a separate body of research showing that driving is impaired by distraction. The two have yet to be integrated: this is critical for lighting design recommendations because giving consideration to distraction may affect the optimal conditions established in lighting studies. A first step in that process is establishing the critical type(s) of distraction that might then be simulated in lighting research. This paper reviews evidence for the prevalence of driving distractions as recorded by two methods: interviews with drivers following collision and observation of drivers on real roads. These data suggest that auditory distractions such as conversation with passengers and listening to music are prevalent distractions, and are therefore appropriate distractions to incorporate in further research of lighting and hazard detection experiments.